Crystal structure of 1-tosyl-1,2,3,4-tetrahydroquinoline - S. Jeyaseelan; K.V. Asha; G. Venkateshappa; P. Raghavendrakumar; B.S. Palakshamurthy (Acta Crystallographica Section E, 2014)
In the title compound, C16H17NO2S, the heterocyclic ring adopts a half-chair conformation and the bond-angle sum at the N atom is 350.2°. The dihedral angle between the planes of the aromatic rings is 47.74 (10)°. In the crystal, molecules are linked by C—H...O hydrogen bonds to generate [010] chains.